Gandhi's thought and liberal democracy - Lall, Sanjaya (Studies in comparative philosophy and religion, 2019)
Overview of Gandhian thought -- Gandhi's thought and liberal democracy -- Modern day freedom from Gandhi's perspective -- Gandhi's religious thought as compatible with and conducive to liberalism -- On practical aspects -- Gandhi and liberal rights.